Man and woman alone and together - Cook, Kaye V.; Lee, Lance L. (Wheaton. IL BridgePoint, 1992)
Includes bibliographical references and index.
Keywords: Sex role -- religious aspects -- Christianity; Sex role -- Biblical teaching; Men (Christian theology).; Women (Christian theology).; Interpersonal relations -- Biblical teaching